PENINGKATAN PERTUMBUHAN DAN HASIL KACANG TANAH (Arachis hypogea L.) AKIBAT PEMBERIAN TAKARAN PUPUK KANDANG DOMBA DAN KONSENTRASI PUPUK ORGANIK CAIR TRUBUS - Raden Budiasih (Paspalum: Jurnal Ilmiah Pertanian, 2015)
We report the dose of sheep manure and POC concentration Poster which aims to study changes in the dose of sheep manure and Poster POC concentration on growth and yield of peanut (Arachis hypogea L.). This research is compiled in a randomized block design (RAK) factorial design consisting of two factors. The first factor sheep manure dosage form consists of three levels ie d1 (5 t ha-1), d2 (10 ton ha-1) and d3 (15 ton ha). The second factor in the form of the concentration of liquid organic fertilizer Poster consists of three levels ie p1 (1 ml-1), p2 (3 ml l-1) and P3 (5 ml l-1), respectively - each combination treatment was repeated 3 times. Different test average - average use multiplerange test duncant 5% significance level. Award dose sheep manure and POC concentration Poster melihatkan their interaction on plant height 9 MST, pong numberper plant and weight of pods per plant, giving a high dose of manure that requires  concentration POC rendah. Secara an Independent Award dose effect of manure 10 ton ha-1 and 15 ton ha-1 showed the best effect on the plant height ages 5 and 7 MST MST, the percentage of pithy pods and number of seeds per plant.